Challenges to Engineering Design Teamwork in a Remote Learning Environment - Elise Belanger; James Moller; Jinjuan She (MDPI AG, 2022)
Remote team collaboration was not familiar to many engineering students before COVID-19. The rapid shift from in-person to remote during the pandemic caused dramatic challenges, especially for freshmen and sophomore students in engineering design classes, where teamwork is typically needed to explore both the problem and solution spaces for ill-defined problems and students have had little previous design project experience. This study aims to explore challenges revealed by students in remote design collaboration through the lens of a sophomore-level class about early-stage engineering design. The authors closely observed team members' struggles through three datasets collected in one semester: (1) team performance and survey responses in an in-class idea generation activity; (2) individual student final reflection essays about their semester-long team project at the end of the semester; and (3) bi-weekly individual reflections on the discussion board throughout the entire semester. Unlike the classic findings that sketches improve performance, we found significant positive correlations between teamwork experience (e.g., communication, efficiency, perceived contribution) and the number of ideas expressed in text, and significant negative correlations between teamwork experience and number of ideas expressed in a combination of sketches and text. Therefore, we propose educators should also work on improving students' ability to express design ideas with text descriptions, on top of traditionally emphasized visual representations. In addition, we found the remote environment exacerbated existing team challenges more than it created new challenges. The remote-related challenges also dropped dramatically after the first few weeks and then remained steady. The remote-related challenges and their changing patterns indicate large potential to improve remote design collaboration.